PREVALENCE AND SPATIAL DISTRIBUTION OF ECTOPARASITES IN Wallago attu OF RIVER PENNA, YSR DISTRICT, ANDHRA PRADESH, INDIA (Applied Biological Research, 2023)
An ectoparasitic survey on fish Wallago attu (n = 95) of river Penna, YSR  district, Andhra Pradesh (India) was executed from August, 2017 to  February, 2018. A total of 3202 parasites belonging three ectoparasitic  groups viz., three monogeneans - Thaparocleidus indicus, thaparocleidus  wallagonius, Mizelleus indicus, one copepod - Ergasilus malnadensis, and  one isopod - Alitropus typus were detected from the gills of the examined  hosts. Their spatial distributions on the host gills were reported. Only E.  malnadensis, T. wallagonius and T. indicus showed aggregate distribution  while the remaining two species, M. indicus and A. typus showed random  distribution. Only, A. typus, T. wallagonius and T. indicus showed positive  and statistically significant correlation with the condition factor. Location  wise ectoparasite analysis revealed the higher infestation rates in site-II  Somasila backwaters, Vontimitta compared to site-I Chennur. Spatial  distribution studies revealed that there is no significant preference for the  sides of the host fish. Both the sides of gill arch wereequally infected.  However, they showed preference within the gill arches. Monogeneans  preferred gill arches II, III and IV, whereas copepods and isopods  preferred gill arches I and II. There was meagre effect of host size and host  sex on the ectoparasitic infection. These types of spatial distribution studies  give an accurate location of the parasites to apply the eradication measures  and eradicate them efficiently in fish aquaculture.
Keywords: Ectoparasites; mean intensity; prevalence; spatial distribution